Revisits within 48 Hours to a Thai Emergency Department - Jiraporn Sri-on; Adisak Nithimathachoke; Gregory Philip Tirrell; Sataporn Surawongwattana; Shan Woo Liu (Emergency Medicine International)
Objective. Emergency department (ED) revisits are a common ED quality measure. This study was undertaken to ascertain the contributing factors of revisits within 48 hours to a Thai ED and to explore physician-related, illness-related, and patient-related factors behind those revisits. Methods. This study was a chart review from one tertiary care, urban Thai hospital from October 1, 2009, to September 31, 2010. We identified patients who returned to the ED within 48 hours for the same or related complaints after their initial discharge. Three physicians classified revisit as physician-related, illness-related, and patient-related factors. Results. Our study included 172 ED patients’ charts. 86/172 (50%) were male and the mean age was 38 ± 5.6 (SD) years. The ED revisits contributing factors were physician-related factors [86/172 (50.0%)], illness-related factors [61/172 (35.5%)], and patient-related factor [25/172 (14.5%)], respectively. Among revisits classified as physician-related factors, 40/86 (46.5%) revisits were due to misdiagnosis and 36/86 (41.9%) were due to suboptimal management. Abdominal pain [27/86 (31.4%)] was the majority of physician-related chief complaints, followed by fever [16/86 (18.6%)] and dyspnea [15/86 (17.4%)]. Conclusion. Misdiagnosis and suboptimal management contributed to half of the 48-hour repeat ED visits in this Thai hospital.